Hubungan antara Durasi Jam Layanan Klinis dengan Gejala Permasalahan Suara pada Terapis Wicara di Kabupaten Sleman Yogyakarta - Laksmita, Nurul; Fitri, Anisyah Dewi Syah (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: In Indonesia, the increasing number of patients who require Speech Therapy treatment is inversely proportional to the number of Speech Therapists. in some health facilities that have Speech Therapy services there is a buildup of patients which causes Speech Therapists to treat more than 6 (six) patients per day. This can make Speech Therapists vulnerable to voice problems. Variations of voice problems that arise include throat discomfort, vocal fatigue, and hoarseness. Objectives: To determine the relationship between the duration of clinical service hours and symptoms of voice problems in Speech Therapists in Kabupaten Sleman Yogyakarta. Methods: This research is a type of quantitative research and correlation study research design with cross sectional data collection. The data collection technique in this study used a total sampling technique of 60 respondents. The data collected will be analyzed statistically using the Spearman Rank Correlation test. Results: The results of the analysis test show that the sig value of 0.001 is smaller than 0.05 (0.001<0.05) so that there is a relationship between the duration of clinical service hours and symptoms of voice problems in Speech Therapists in Kabupaten Sleman Yogyakarta. In addition, there is a coefficient of 0.409 indicating that the variable duration of clinical service hours and symptoms of voice problems have a significant positive correlation. Conclusion: Based on the results of the data analysis, it can be concluded that there is a significant relationship between the duration of clinical service hours and symptoms of voice problems in Speech Therapists in Kabupaten Sleman Yogyakarta. This shows that the higher the duration of clinical service hours, the higher the symptoms of voice problems. Keywords: Duration of Clinical Service Hours, Voice Problems, Speech Therapist